Integrasi Nasional dalam Rangka Persatuan dan Kesatuan Bangsa - Nabila, Dienda Zarmi; Kurniawati, Ice; Handayani, Nurul; Hasanah, Nur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
National integration is the process of uniting various social and cultural groups in a country to form a harmonious unity. National integration is an effort to integrate ethnic, religious, linguistic, and cultural diversity into a solid national unity. This research utilizes the library research method, which involves analysis and learning from various reference sources, journal articles, books, and previous research The main source of data is research articles published in the last 10 years through the google scholar website. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the national integration process involves various aspects, such as education that prioritizes national values, policies for equitable development, and fair law enforcement. In addition, community participation in maintaining harmony between groups and promoting tolerance is also very crucial. The challenges faced in national integration include the potential for disintegration due to differences in interests and social injustices, as well as the threat of ideologies that are contrary to the values of Pancasila